Fylgikvillar blaðnámsaðgerða við lungnakrabbameini á Íslandi 1999-2008 - Rut Skúladóttir; Gudrún Nína Óskarsdóttir; Helgi J. Ísaksson; Steinn Jónsson; Húnbogi Þorsteinsson; Tómas Guðbjartsson (Læknafélag Íslands, Læknafélag Reykjavíkur, 2010)
Neðst á síðunni er hægt að nálgast greinina í heild sinni með því að smella á hlekkinn Skoða/Opna(view/open) OBJECTIVE: Non small cell lung cancer (NSCLC) is the second most common cancer in Iceland. We studied the indications and surgical outcome of lobectomy for NSCLC in Iceland. MATERIALS AND METHODS: 213 consecutive patients underwent lobectomy for NSCLC between 1999 and 2008. Data on indications, histology, TNM-stage and complications were analysed, and logistic regression used to assess outcome predictors. RESULTS: The majority of patients (60%) were referred because of symptoms, whereas 40% were asymptomatic. Adenocarcinoma (62%) and squamous cell carcinoma (29%) were the most frequent histological types. Operative staging showed that 59.6% of cases were stage I, 17.8% were stage II, 7% were stage IIIA and 14.6% were stage IIIB or IV. Mediastinoscopy was performed in 13.6% of cases. Mean operative time was 128 min., operative bleeding 580 ml and median hospital stay 10 days. Sixteen patients (7.5%) had major complications and 36 (17.5%) had minor complications, such as atrial fibrillation and pneumonia. Twelve patients required reoperation, most often due to bleeding, but two had empyema and one had a bronchopleural fistula. Older patients with high ASA scores and extensive smoking history were at increased risk for complications. No patient died within 30 days of surgery whereas two (0,9%) died within 90 days of surgery. CONCLUSIONS: The results of lobectomy for NSCLC in Iceland are excellent in relation to operative mortality and short term complications. Inngangur: Lungnakrabbamein er annað algengasta krabbamein á Íslandi og það sem dregur flesta til dauða. Skurðaðgerð er helsta meðferðin og langoftast er beitt blaðnámi. Markmið þessarar rannsóknar var að kanna ábendingar og snemmkomna fylgikvilla blaðnáms á Íslandi. Efniviður og aðferðir: 213 sjúklingar sem gengust undir blaðnám vegna lungnakrabbameins á árunum 1999-2008. Kannaðar voru ábendingar, fylgikvillar, æxlisgerð og TNM-stigun. ...